2012
DOI: 10.1080/07481187.2011.553324
|View full text |Cite
|
Sign up to set email alerts
|

Goals Set in the Land of the Living/Dying: A Longitudinal Study of Patients Living with Advanced Cancer

Abstract: A longitudinal qualitative research study was undertaken to provide an understanding of a prolonged experience of advanced cancer, as seen through the eyes of dying individuals. Using a variant of the grounded theory method, the authors theoretically sampled, from outpatient clinics in a large comprehensive cancer treatment center, 27 patients with either advanced lung or gastrointestinal cancer who had an expected survival of up to 2 years. The authors conducted a total of 54 interviews with these patients to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(94 citation statements)
references
References 47 publications
1
93
0
Order By: Relevance
“…Specific themes found in other research are echoed here, including lack of control over bodies (Chapple & Ziebland, 2002;Kelly, 2008), bodily changes as warnings of impending death Sand et al, 2009), uncertainty and unknowing during the palliative care stage (Nissim, et al, 2012), feelings of social separation ( Koffman et al, 2012) and existential loneliness (Strang & Sand, 2006). Similarly, other research has found that cancer survivors and those living with advanced cancer show an increased awareness of time, difficulty in reflecting on future time and sense of a receding future (Cecil et al, 2010;Rasmussen & Elverdam, 2007).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Specific themes found in other research are echoed here, including lack of control over bodies (Chapple & Ziebland, 2002;Kelly, 2008), bodily changes as warnings of impending death Sand et al, 2009), uncertainty and unknowing during the palliative care stage (Nissim, et al, 2012), feelings of social separation ( Koffman et al, 2012) and existential loneliness (Strang & Sand, 2006). Similarly, other research has found that cancer survivors and those living with advanced cancer show an increased awareness of time, difficulty in reflecting on future time and sense of a receding future (Cecil et al, 2010;Rasmussen & Elverdam, 2007).…”
Section: Discussionmentioning
confidence: 84%
“…It adds to the existing literature through its focus on those living at home with advanced cancer. In contrast previous studies have tended to concentrate on hospice settings without taking into account those who may be living for years with the knowledge of their terminal prognosis (Nissim et al, 2012).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…These patients may benefit from tailored interventions that help them adjust specifically to the recurrence with emphasis on identifying ways to maintain participation in life events. Planning treatment or expected fatigue around everyday events such as children's activities or work hours may allow these people to transition to living with cancer or "reclaim" meaningful aspects of their lives after a period of treatment (Nissim et al, 2012). In either case, patients and their families may be able to retain some normalcy and mitigate the effects of the illness experience.…”
Section: Discussionmentioning
confidence: 95%